2006
DOI: 10.1111/j.1348-0421.2006.tb03849.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intracerebral Immunization against Pseudorabies Virus in Mice

Abstract: Abstract:To evaluate the efficacy of intracerebral (IC) immunization, mice were immunized with formalininactivated pseudorabies virus (PRV) by either subcutaneous (SC) or IC injection, and then 10 6 plaqueforming units of PRV were introduced into the hindleg of the immunized or non-immunized mice by intramuscular injection. The antibody titer in serum was elevated and boosted by additional immunization via both the SC and IC routes, but was higher after IC immunization. Intracerebrally immunized mice were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…This can be surprising as the nervous system is an immuno specialized organ where directly injected viruses evade an immune response, probably through the installation of an immunosuppressive milieu . However, this is not the case when antigens or virus particles are delivered by intrathecal immunization Harling-Berg et al, 1991;Panda et al, 1965;Stevenson et al, 1997;Shin et al, 2006). It is likely that after IC inoculation of the CDV, virus induced leakage of neural cells and redirected viral antigens to the cerebrospinal fluid, the meninges and finally to the cervical lymph nodes (Hatterer et al, 2006).…”
Section: -Discussionmentioning
confidence: 99%
“…This can be surprising as the nervous system is an immuno specialized organ where directly injected viruses evade an immune response, probably through the installation of an immunosuppressive milieu . However, this is not the case when antigens or virus particles are delivered by intrathecal immunization Harling-Berg et al, 1991;Panda et al, 1965;Stevenson et al, 1997;Shin et al, 2006). It is likely that after IC inoculation of the CDV, virus induced leakage of neural cells and redirected viral antigens to the cerebrospinal fluid, the meninges and finally to the cervical lymph nodes (Hatterer et al, 2006).…”
Section: -Discussionmentioning
confidence: 99%
“…Many neurotropic infectious agents including rabies virus [11], herpes viruses [23,30], corona viruses [25], Bornavirus [14], enterovirus [15] and influenza virus [20,21,24,31] invade the central nervous system (CNS) from the periphery via transneural spread. The protective effect of immunization via ordinary routes is limited for the transneural spread of viruses, since it may result from humoral antibodies that simply neutralize the viruses before they infect nerve cells [37][38][39].…”
mentioning
confidence: 99%
“…We have previously shown that intrathecal immunization with inactivated pseudorabies virus, a neurotropic virus, completely protected the animals against lethal virus challenge, whereas all non-immunized and several subcutaneously immunized mice died after developing neurological signs [20]. Previous reports have shown that immunization via the brain or CSF elicits systemic humoral immune responses in the cervical lymph nodes, spleen, serum and CSF [7,8,19].…”
mentioning
confidence: 99%
“…We previously reported that higher serum antibody titers were observed in mice after intracerebral immunization with inactivated pseudorabies virus than SC immunization [20].…”
mentioning
confidence: 99%